WICKED PROBLEMS AND THE DESIGN THINKING METHOD AS A TOOL TO SOLVE THESE PROBLEMS. THE CASE ALIEN PROJECT - Magdalena PROCZEK; Marta GARBARCZYK (Eastern European Journal of Regional Studies, 2023)
Today's global challenges are characterized by increasing complexity. This makes it possible to ‎call these challenges so-called wicked problems, which are difficult to define clearly, have no ‎single solution and require the involvement of multiple stakeholders for its purpose. Such ‎complication can include a group of contemporary migration and refugee problems, which include ‎dilemma of adaptation and integration of immigrants, or social conflicts between locals and ‎newcomers, etc. The Design Thinking (DT) method, which is recipient- and user-oriented ‎solution, can be used to try to solve these issues. Importantly, the beneficiaries themselves ‎can also be involved.‎ The purpose of this study is to present the essence of wicked problems, as well as the DT ‎method as a tool for solving contemporary problems, including migration and refugees. The ‎study fills the research gap on presenting a proposal for a tool in the form of the Design Thinking ‎method for solving contemporary wicked problems, including in the setting of migrants and ‎refugees, using the results of the ALIEN project as an example. A synthetic review of the literature on wicked problems was also conducted.‎ The study used a qualitative method in the form of logical inference, as well as a review ‎of the literature on the subject, studies, and reports. By addressing this issue, the authors ‎intended to expand the existing body of global analysis in this area.‎ As demonstrated in this paper, the DT method has been successfully used to solve ‎wicked problems among migrants and refugees in Norway as well as Ethiopia, Senegal, USA, ‎Colombia, Australia, France, Germany, Greece, Jordan and Iraq. International research ‎teams, including the ALIEN project team, are seeking effective solutions to wicked problems ‎accompanying migration and refugee processes. This empirical study discusses the application ‎of this method to solving wicked problems surrounding migrants and refugees, especially their ‎solution proposals developed within the ERASMUS+ ALIEN Strategic Partnerships project. ‎The authors believe that they could be successfully used today on a large scale.